2015
DOI: 10.1007/978-3-319-17837-0_12
|View full text |Cite
|
Sign up to set email alerts
|

The RISCOSS Platform for Risk Management in Open Source Software Adoption

Abstract: Abstract. Managing risks related to OSS adoption is a must for organizations that need to smoothly integrate OSS-related practices in their development processes. Adequate tool support may pave the road to effective risk management and ensure the sustainability of such activity. In this paper, we present the RISCOSS platform for managing risks in OSS adoption. RISCOSS builds upon a highly configurable data model that allows customization to several types of scopes. It implements two different working modes: ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…For instance, it is reported that they fail on considering risk factors [20]. We envisage the need to provide full support to strategic decision making based on the analysis of the impact of QRs in such key criteria, reconciling: 1) QR-specific universes of discourse with definition of the concepts that matter in their management and assessment [17], 2) reasoning frameworks as the NFR framework [15], 3) a highly informative dashboard that provides full transparency to the decision making process [21].…”
Section: State Of the Artmentioning
confidence: 99%
“…For instance, it is reported that they fail on considering risk factors [20]. We envisage the need to provide full support to strategic decision making based on the analysis of the impact of QRs in such key criteria, reconciling: 1) QR-specific universes of discourse with definition of the concepts that matter in their management and assessment [17], 2) reasoning frameworks as the NFR framework [15], 3) a highly informative dashboard that provides full transparency to the decision making process [21].…”
Section: State Of the Artmentioning
confidence: 99%
“…• Introducing the different capabilities of a risk analysis supporting platform [9]. The briefing considers the results of an EU project called RISCOSS (www.riscoss.eu) that has developed a software platform that implements this 3-layer view.…”
Section: Motivation and Objectivesmentioning
confidence: 99%
“…A set of scientific papers produced in the RISCOSS project serve to document the main concepts presented [3][6] [7] [8]. As for tool support, during the briefing we use the RISCOSS platform [9]. The current version of the platform can be accessed at https://github.com/RISCOSS/riscoss-corporate.…”
Section: Introductionmentioning
confidence: 99%
“…business software projects incorporating Open Source Software (OSS) components (Synopsys, 2020;Tidelift, 2019;Szulik, 2018). Managers and practitioners in software-intensive businesses using CBSD frequently make decisions concerning the adoption of OSS components to be integrated into their tools and products (Franch et al, 2015;López L. Costal et al, 2016;Hauge et al, 2009Hauge et al, , 2010Stol and Ali Babar, 2010a;Ayala et al, 2011a;Lundell et al, 2017;Lenarduzzi et al, 2019;Spinellis, 2019;Kazimierczak et al, 2020). A key economic motivation for many businesses is the use of OSS as a means of short-cutting resource intensive software development processes (Spinellis, 2019;European Commission, 2017;Kazimierczak et al, 2020;Petersen et al, 2018;Badampudi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of OSS component adoption is more complex and nuanced than simply identifying functionally suitable software (Spinellis, 2019). Businesses need to consider multiple additional factors, for example, the software licence of the component in the context of their own licensing policy (Stol and Ali Babar, 2010a;van der Burg et al, 2014;Spinellis, 2019;Petersen et al, 2018), and also the viability and stability of the OSS project community that develops the component (Stol and Ali Babar, 2010a;TODO Goup, 2018;Franch et al, 2015;López L. Costal et al, 2015.…”
Section: Introductionmentioning
confidence: 99%